2019
DOI: 10.29252/nfsr.6.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Semi Ready-to-Eat Shrimp Soup Powder and Assessment of Its Shelf Life

Abstract: Background and Objectives: Macrobrachium nipponense are wetland crustaceans. The shrimp is rich in protein and unsaturated fatty acids (FAs). Therefore, the aim of this study was to use M. nipponense as a supplement for the preparation of a new soup. Materials and Methods: Nearly 40 kg of M. nipponense were harvested from Anzali Lagoon, Northern Iran. Shrimps were washed and dipped in NaCl solution (10% w/v) with a ratio of 1 to 2 at boiling temperature for 3 min. Then, these were cooled down for 10 minutes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Akuamoa et al (2018) found the ash content 13.80 ± 0.09% to 15.42 ± 0.09% in dry smoked Penaeus notialis. Zarehgashti et al (2019) found the ash content 9.33±0.00% in dried shrimp meat. Rosemary et al (2020) reported the ash content 10.34±0.72% in market dried shrimp and 8.95±0.07% in the home dried shrimp.…”
Section: Ash Contentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Akuamoa et al (2018) found the ash content 13.80 ± 0.09% to 15.42 ± 0.09% in dry smoked Penaeus notialis. Zarehgashti et al (2019) found the ash content 9.33±0.00% in dried shrimp meat. Rosemary et al (2020) reported the ash content 10.34±0.72% in market dried shrimp and 8.95±0.07% in the home dried shrimp.…”
Section: Ash Contentsmentioning
confidence: 93%
“…Ravichandran et al (2009) also reported the protein content of flesh of white shrimp to be 41.30% whereas the shell contained 32.5%. Zarehgashti et al (2019) stated the protein content in dried shrimp meat was 72.74 ±1.99% of dry weight. So the protein content of dried shrimp products in the present study could be compared with the previous reports.…”
Section: Protein Contentsmentioning
confidence: 98%
“…r Storage stability of ready-to-cook soup mixes at accelerated shelf-life testing The chemical composition, microbial contamination, storage conditions and type of packaging play an important role in the shelf-life of food products [Zarehgashti et al, 2019]. In our study, based on consumer assessment results, it was decided to evaluate the shelf--life of only RTC MPHS mix as the most promising formulation with the fish-derive additive.…”
Section: Consumer Assessmentmentioning
confidence: 99%